The Role of NR4A1 in the Pathophysiology of Osteosarcoma: A Comprehensive Bioinformatics Analysis of the Single-Cell RNA Sequencing Dataset - Liu, Weidong; Hao, Yuedong; Tian, Xiao; Jiang, Jing; Qiu, Quanhe (Frontiers in Oncology, 2022)
Osteosarcoma is a kind of aggressive human malignancy and the prognosis of the patients with osteosarcoma remains low. Studies have demonstrated that tumor microenvironment plays a key role in regulating osteosarcoma progression. Recent studies also showed that scRNA-seq play an essential role in understanding tumor heterogeneity and distinct subpopulations of tumors. In order to further understand scRNA-seq data of osteosarcoma tissues, the present study further analysed the scRNA-seq dataset (GSE152048) and explored the potential role of nuclear receptor-related genes in the pathophysiology of osteosarcoma. In our analysis, we identified 11 cell types in all the osteosarcoma tissues and nuclear receptors (NRs) were distributed in all types of cells. Further stratification analysis showed that NRs were mainly detected in “TIL”, “Osteoblastic” of the metastasis osteosarcoma, and in “TIL”, “Myoblast”, “Endothelial” and “Myeloid” of the primary osteosarcoma, and in “Chondroblastic”, “Osteoblast” and “Pericyte” of the recurrent osteosarcoma. The NRs were also differentially expressed in different cell types among the metastasis, primary and recurrent osteosarcoma. Furthermore, several NRs such as NR4A2, NR4A1, NR3C1 have been found to be differentially expressed in most types of DEGs among metastasis, primary and recurrent osteosarcoma. High expression of NR4A1 in the osteosarcoma tissues was significantly correlated with shorter 5-year overall survival of patients with osteosarcoma. On the other hand, there was no significant association between NR4A2 expression and the 5-year overall survival of patients with osteosarcoma. The expression of NR4A1 was significantly higher in the metastasis osteosarcoma tissues than that in the primary osteosarcoma tissues as validated from GSE32981 and GSE154540. The expression of NR4A1 was significantly higher in osteosarcoma tissues from patients with poor chemosensitivity than that from patients with good chemosensitivity as validated from GSE154540. Further analysis of the scRNA-seq data revealed that the percentage of osteoblasts with high NR4A1 expression was higher in the recurrent osteosarcoma tissues than that with low NR4A1 expression. In conclusion, the presents study may suggest that NR4A1 may be an important prognostic biomarker for osteosarcoma progression. However, further validation studies should be performed to confirm our findings.